2020
DOI: 10.1002/ijc.33402
|View full text |Cite
|
Sign up to set email alerts
|

Is the risk of childhood leukaemia associated with socioeconomic measures in Denmark? A nationwide register‐based case‐control study

Abstract: The aetiology of childhood leukaemia is poorly understood. Knowledge about differences in risk by socioeconomic status (SES) may enhance etiologic insights. We conducted a nationwide register‐based case‐control study to evaluate socioeconomic differences in the risk of childhood leukaemia in Denmark and to access whether associations varied by different measures of SES, time point of assessment, leukaemia type and age at diagnosis. We identified all cases of leukaemia in children aged 0 to 19 years, born and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…While most international studies reported evidence of an association between SES and childhood leukemia risk, the observed direction of the association was heterogeneous. Generally, higher SES was associated with higher risk, but rarely also inverse associations were reported 20‐23 . In the absence of consistent and pertinent evidence, we did not adjust our analysis by SES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most international studies reported evidence of an association between SES and childhood leukemia risk, the observed direction of the association was heterogeneous. Generally, higher SES was associated with higher risk, but rarely also inverse associations were reported 20‐23 . In the absence of consistent and pertinent evidence, we did not adjust our analysis by SES.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, higher SES was associated with higher risk, but rarely also inverse associations were reported. [20][21][22][23] In the absence of consistent and pertinent evidence, we did not adjust our analysis by SES.…”
Section: Period (Number Of Cases)mentioning
confidence: 99%
“…For example, geographic differences in socioeconomic status (SES) could be related to the risk of childhood leukemia. Neighborhood SES has been studied for many health outcomes, including childhood leukemia [ 17 , 18 , 19 , 20 , 21 , 22 ]. Area deprivation was not found to be associated with acute lymphoblastic leukemia (ALL) [ 22 ], and childhood leukemia was also not associated with area SES in some studies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood SES has been studied for many health outcomes, including childhood leukemia [ 17 , 18 , 19 , 20 , 21 , 22 ]. Area deprivation was not found to be associated with acute lymphoblastic leukemia (ALL) [ 22 ], and childhood leukemia was also not associated with area SES in some studies [ 19 , 20 ]. However, lowest area SES was found to be associated with lower ALL risk compared with highest area SES [ 21 ], and childhood leukemia incidence in England and Wales was higher in relatively affluent communities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%